2019
DOI: 10.1007/s40094-019-00346-4
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study on the effect of Cu- and Na-substituted layers on spin-dependent transport and TMR in the Fe/ZnO/Fe MTJ

Abstract: Using density functional theory, effects of Na-and Cu-substituted layers on the spin-dependent electronic transport properties of Fe/ZnO/Fe magnetic tunnel junction based on zinc oxide barrier tunnel, with rock-salt crystalline structure, have been studied. In zero-bias voltage, conductance and tunneling magneto-resistance (TMR) ratio of structures are calculated. It is showed that substituted layers in the pristine junction greatly affect conductance and TMR ratio of this junction. The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…type ZnO-based MTJs (Fe/ZnO/Fe) have been investigated in some experimental and theoretical studies before [17][18][19]. They showed that the ZnO barrier exhibit coherent tunneling similar to the conventional MgO barrier.…”
Section: Introductionmentioning
confidence: 99%
“…type ZnO-based MTJs (Fe/ZnO/Fe) have been investigated in some experimental and theoretical studies before [17][18][19]. They showed that the ZnO barrier exhibit coherent tunneling similar to the conventional MgO barrier.…”
Section: Introductionmentioning
confidence: 99%